Respuesta :
Answer:
[tex] \boxed{ \sf{ \bold{- 3}}}[/tex]
Step-by-step explanation:
[tex] \sf{3 - x = 5x + 21}[/tex]
Move 5x to left hand side and change it's sign
⇒[tex] \sf{ - x - 5x + 3 = 21}[/tex]
Move 3 to right hand side and change it's sign
⇒[tex] \sf{ - x - 5x = 21 - 3}[/tex]
Collect like terms
⇒[tex] \sf{ - 6x = 21 - 3}[/tex]
Subtract 3 from 21
⇒[tex] \sf{ - 6x = 18}[/tex]
Divide both sides of the equation by -6
⇒[tex] \sf{ \frac{ - 6x}{ - 6} = \frac{18}{-6}} [/tex]
Calculate
⇒[tex] \sf{x = -3}[/tex]
Hope I helped!
Best regards!!
Answer:
x = - 3
Step-by-step explanation:
3 - x = 5x + 21
- x + 3 = 5x + 21
(- x + 3) + (- 3 - 5x) = (5x + 21) + (- 3 - 5x)
(- x + 3) + (- 5x - 3) = (5x + 21) + (- 5x - 3)
- x + 3 - 5x - 3 = 5x + 21 - 5x - 3
- x - 5x + 3 - 3 = 5x - 5x + 21 - 3
- 6x = 18
x = - 18/6
x = - 3